Thermoluminescence Response of Copper-Doped Potassium Borate Glass Subjected to 6 Megavolt X-Ray Irradiation - Hossain, Imam (Springer New York LLC, 2015)
This study addresses the characteristics of Cu-doped and undoped potassium borate glass for use as ionizing radiation dosimeters by investigating and comparing the thermoluminescence responses, linearity, sensitivity and dose response s of the two types of glasses. A number of samples based on xK2CO3+ (100 – x)H3BO3, where 10 = x = 30 mol.%, have been prepared using a melt quenching technique. The amorphous phases were identified using X-ray diffraction (XRD). The undoped potassium borate samples 20K2CO3+ 80H3BO3(mol.%) and Cu-doped (0.5 mol.%) samples were placed in a solid phantom apparatus and irradiated with in X-ray tube under 6 MV accelerating voltage with doses ranging from 0.5 to 4.0 Gy. This beam was produced by the Primus MLC 3339 linear accelerator (LINAC) available at Hospital Sultan Ismail, Johor Bahru, Malaysia. The results clearly show the superiority of Cu-doped glass in terms of response and sensitivity to producing luminescence over undoped potassium borate glass. The sensitivity of Cu-doped glass is 6.75 times greater than that of undoped glass.